Leveraging Destination Image: The Impact of Integrated Marketing Communication on Visits to Penglipuran Village - Widhiarini, Ni Made Ayu Natih; Yani, Ni Wayan Mega Sari Apri; Wirawan, Putu Eka (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study examines the role of Integrated Marketing Communication (IMC) and consumer behavior in influencing tourists' decisions to visit Penglipuran Tourism Village. This study also analyzes the moderating effect of destination image as a unique and sustainable Balinese traditional village. The results show that the implementation of effective IMC strategies, such as the use of social media and partnerships with educational institutions, as well as an understanding of consumer behavior, can increase the number of tourist visits. The destination image as a unique Balinese traditional village plays an important role in attracting tourists. The implications of this study provide recommendations for destination managers to develop more integrated marketing strategies.